Women and states : norms and hierarchies in international society - Towns, Ann E. , 1970- (Cambridge : Cambridge University Press, 2010)
"Momentous changes in the relation between women and the state have advanced women's status around the globe. Women were barred from public affairs a century ago, yet almost every state now recognizes equal voting rights and exhibits a national policy bureau for the advancement of women. Sex quotas for national legislatures are increasingly common. Ann Towns explains these changes by providing a novel account of how norms work in international society"--Provided by publisher
"Momentous changes in the relation between women and the state have advanced women's status around the globe. Women were barred from public affairs a century ago, yet almost every state now recognizes equal voting rights and exhibits a national policy bureau for the advancement of women. Sex quotas for national legislatures are increasingly common. Ann Towns explains these changes by providing a novel account of how norms work in international society. She argues that norms don't just provide standards for states, they rank them, providing comparative judgments which place states in hierarchical social orders. This focus on the link between norms and ranking hierarchies helps better account for how a new policy, such as equality for women in public life, is spread around the world. Women and States thus offers a new account of the relationship between women and the state, and of the influence of norms in international politics"--Provided by publisher
1. Introduction -- 2. Constructivism and world-wide changes in state policy -- 3. A complex society of norms and social hierarchies -- 4. Excluding women in the society of civilized states -- 5. Women's suffrage and the standards of civilization -- 6. National women's policy bureaus and the standards of development -- 7. Legislature sex quotas and cultural rank -- 8. Conclusion
Includes bibliographical references (p. 214-241) and index
Keywords: Women's rights -- History; Women -- Social conditions